The Mentimeter Media-Assisted Problem-Solving Model on Elementary School Students' Creativity and Learning Outcomes - Sare, Claudion Kanigia; Saptono, Bambang; Handayani, Mella Indra; Anggriani, Mitha Dwi (International Journal of Elementary Education, 2024)
Indonesian language education in elementary schools requires innovative pedagogical interventions due to major challenges such as student disengagement, suboptimal learning outcomes, and a lack of creativity development. This research aims to analyze the effect of differences in student learning outcomes between those taught using problem solving assisted by mentimeter media and using an expository approach in learning Indonesian. This research uses a quasi-experimental design with a non-equivalent control group design. The research population consisted of all fifth grade students at elementary schools in Sewon Bantul, with a sample of 87 students selected using a purposive cluster random sampling technique. The sample was divided into two groups: the experimental group (44 students) who used the problem-solving learning strategy assisted by Mentimeter media, and the control group (41 students) who used an expository approach. The research instrument used was a test, and data analysis was carried out using descriptive analysis and inferential statistical analysis using the paired sample t-test and the independent sample t-test. The results of the research show that the use of problem-solving learning strategies assisted by mentimeter media has a significant influence on increasing student creativity (0.000 < 0.05) and student learning outcomes (0.000 < 0.05). Apart from that, there are significant differences in creativity and learning outcomes between groups of students taught with problem solving assisted by Mentimeter media and an expository approach to learning Indonesian (0.000 < 0.05).